Applications and Advancements of 3D Printing in Construction (Sebha University Conference Proceedings, 2024)
Recent years have seen tremendous developments in the building business, with one of the most revolutionary technologies being 3D printing (3DP). Additive manufacturing, or 3DP, has emerged as a significant advancement in several industries, including construction. This review attempts to provide a thorough grasp of the current and future condition of 3DP in the construction sector by reviewing a large number of research, case studies, and industry reports. This study offers a thorough analysis of 3DP in the construction industry, examining the uses, difficulties, and potential of the technology. It provides an overview of several 3DP construction methods, identifies the required tools, and includes information on printer kinds and materials. The paper discusses the advantages of 3DP in construction, such as reduced material waste, increased design freedom, and faster building schedules. The limitations and drawbacks of 3DP in the construction sector are also covered, along with issues with primary costs, regulations, and quality control. Examples of uses for 3DP construction prototypes throughout the world are presented. There is a discussion of the many applications of 3DP in buildings, ranging from large-scale structures to small-scale prototypes. The study's conclusion outlines probable future advancements and 3DP technological breakthroughs that could drastically alter the construction industry.